Determinants of Toilet Training Awareness among Mothers in Siddharthnagar Municipality of Rupandehi District, Nepal - Bhattarai, Sigma; Bhusal, Chet Kant (Journal of Karnali Academy of Health Sciences, 2023)
Introduction: If children are not trained in toilet training, they may have psychological issues. Mother’s alertness playsa very important role in toilet training which is vital for the better growth and development of a child. Thus the objectiveof the study was to assess the determinants of awareness regarding toilet training among mothers.Methods: Descriptive cross-sectional study design was carried out among 100 mothers of children aged 1-3 years usingnon- probability purposive sampling technique. The study was done in Siddharthnagar Municipality-3, Rupandehi Nepal from 19th September to 3rd October 2021. Semi-structured questionnaire was used to collect the data.The collected data was reviewed, coded, entered in Microsoft excel and analyzed by using SPSS version 20. Inferential statistics was used to find the determinants of awareness level.Results: The study findings revealed 49% of mothers had high level of awareness regarding toilet training. Mothershaving age group 31 to 40 years (AOR=12.27; CI: 2.87-52.49), who cannot read and write (AOR=0.09; CI: 0.02-0.52),and number of living children (AOR=36.58; CI: 6.26-213.55) were significantly associated with level of toilet trainingawareness.Conclusion: Almost half of the mothers had high level of awareness regarding toilet training. Age of mother, educationstatus of mother and number of children were determinants of toilet training awareness of mother. Thus, local government,policy makers and health personnel are recommended to conduct informal educational program especially for early agemothers and mothers having only one child for promoting and upgrading the mother’s awareness regarding toilet training.